„Przyszła powódź i zgubiła”. O sposobach przedstawiania Męki Pańskiej w kazaniu wielkopiątkowym Mikołaja Szomowskiego - Kuran, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article refers to the Good Friday sermon (Raj niebieski na ziemi, potopem złości i okrucieństwa żydowskiego zniesiony […], 1655) of baroque preacher, Mikołaj Szomowski. The paper shows the methods of the descriptions the Passion. Two crucial issues are a conceptus and an amplificatio. The idea is taken from principal biblical metaphor — flood. It dominates the whole sermon. Amplification (mainly congeries oraz incrementum) takes place on the two planes — res and verba.